2022
DOI: 10.1128/iai.00417-22
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Roles for Toll-Like Receptors 2 and 9 in the Pathogenesis of Staphylococcus aureus Osteomyelitis

Abstract: Staphylococcus aureus is the major causative agent of bacterial osteomyelitis, an invasive infection of bone. Inflammation generated by the immune response to S. aureus contributes to bone damage by altering bone homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
1
1
Order By: Relevance
“…This effect was not seen for SE planktonic CM which reflects the differences in virulence between SA and SE. Our results are, however, in contrast to a study showing that stimulation of RANKL-primed BMDMs with SA supernatants promotes osteoclastogenesis TLR dependently [ 49 ], indicating that there might also be variations between SA strains.…”
Section: Discussioncontrasting
confidence: 99%
“…This effect was not seen for SE planktonic CM which reflects the differences in virulence between SA and SE. Our results are, however, in contrast to a study showing that stimulation of RANKL-primed BMDMs with SA supernatants promotes osteoclastogenesis TLR dependently [ 49 ], indicating that there might also be variations between SA strains.…”
Section: Discussioncontrasting
confidence: 99%
“…All TLRs but TLR2 and TLR4 are downregulated during osteoclast differentiation, and relative timing of TLR and RANKL/MCSF stimulation of osteoclast precursors elicit opposite effect on osteoclast formation ( 9 ). Very recently it has been reported that TLR2 and TLR9 signaling contributes marginally to the inflammatory bone loss and enhanced osteoclast formation that accompany S. aureus -dependent osteomyelitis (see Osteoclasts and their progenitors ) ( 10 ). However, it is generally accepted that osteoblasts use TLRs and NODs to recognize and respond to S. aureus , which leads to secretion of the master osteoclastogenic cytokine RANKL as well as other factors ( 11 ), as discussed below.…”
Section: Introductionmentioning
confidence: 99%